High miR-30 Expression Associates with Improved Breast Cancer Patient Survival and Treatment Outcome - Jamshidi Maral; Fagerholm Rainer; Muranen Taru A.; Kaur Sippy; Potdar Swapnil; Khan Sofia; Netti Eliisa; Mpindi John-Patrick; Yadav Bhagwan; Kiiski Johanna I.; Aittomäki Kristiina; Heikkilä Päivi; et al. (MDPI, 2022)
Simple Summary Previous research on the miR-30 family and breast cancer patient survival and on miR-30-related chemosensitivity prompted us to design a comprehensive study on the role of the miR-30 family in general and on miR-30d in particular in breast cancer. We present a study consisting of a tumor microarray analysis of 1238 breast cancer patients, a survival analysis, a drug-sensitivity screen with six breast cancer cell lines, and an in-silico pathway analysis. In our analysis, high miR-30d expression was associated with improved survival in breast cancer patients with aggressive tumor phenotypes. In the drug-sensitivity analysis, ectopic expression of miR-30 family members sensitized the cell lines to the treatment. The pathway analysis based on miRNA and mRNA expression in the METABRIC data suggested that the miR-30 family may have an inhibitory role in pathways contributing to EMT and metastasis. Our results suggest prognostic and predictive potential for the miR-30 family for further investigation. Deregulated miRNA expression has been suggested in several stages of breast cancer pathogenesis. We have studied the miR-30 family, in particular miR-30d, in relation to breast cancer patient survival and treatment outcomes. With tumor specimens from 1238 breast cancer patients, we analyzed the association of miR-30d expression with tumor characteristics with the 5-year occurrence of breast cancer-specific death or distant metastasis (BDDM), and with 10-year breast cancer survival (BCS). We conducted a two-stage drug-screen to investigate the impact of miR-30 family members (miR-30a-30e) on sensitivity to doxorubicin and lapatinib in six breast cancer cell lines HCC1937, HCC1954, MDA-MB-361, MCF7, MDA-MB-436 and CAL-120, using drug sensitivity scores (DSS) to compare the miR-30 family mimics to their specific inhibitors. The study was complemented with Ingenuity Pathway Analysis (IPA) with the METABRIC data. We found that while high miR-30d expression is typical for aggressive tumors, it predicts better metastasis-free (p(BDDM) = 0.035, HR = 0.63, 95% CI = 0.4-0.9) and breast cancer-specific survival (p(BCS) = 0.018, HR = 0.61, 95% CI = 0.4-0.9), especially in HER2-positive (p(BDDM) = 0.0009), ER-negative (p(BDDM) = 0.003), p53-positive (p(BDDM) = 0.011), and highly proliferating (p(BDDM) = 0.0004) subgroups, and after adjuvant chemotherapy (p(BDDM) = 0.035). MiR-30d predicted survival independently of standard prognostic markers (p(BDDM) = 0.0004). In the drug-screening test, the miR-30 family sensitized the HER2-positive HCC1954 cell line to lapatinib (p < 10(-2)) and HCC1937, MDA-MB-361, MDA-MB-436 and CAL120 to doxorubicin (p < 10(-4)) with an opposite impact on MCF7. According to the pathway analysis, the miR-30 family has a suppressive effect on cell motility and metastasis in breast cancer. Our results suggest prognostic and predictive potential for the miR-30 family, which warrants further investigation.